Keseimbangan Lini Perakitan Pada Komponen Fuselage Pesawat NC212 Menggunakan Metode RPW dan RA di PT XYZ (Studi Kasus: Komponen Nose Fuselage) - Shanty Nurhalizah; Muhamad As’adi; Santika Sari (Journal of Optimization System and Ergonomy Implementation, 2024)
PT XYZ is a company operating in the aviation industry. The problem faced by the company is an imbalance in the nose fuselage component assembly line. The imbalance is caused by operators not having the appropriate skills for the NC212 aircraft assembly process, and the availability of hand tools not being proportional to the number of operators, as well as delays in the supply of parts to the assembly line. The aim of this research is to identify the balance level of the NC212 aircraft nose fuselage assembly line under actual conditions, and provide suggestions for improvements to improve the balance of the nose fuselage component assembly line. This research method is the Ranked Positional Weight method and the Region Approach. This research uses Arena software to simulate actual conditions and proposed improvements. Based on the results of data processing, the line efficiency was 16.12%, the balance delay was 83.88%, and the smoothness index was 4937.70 with 34 work stations for actual conditions, and the Region Approach method was obtained as the best line balancing method with the percentage of line efficiency of 28.33%, balance delay of 71.67%, and smoothness index of 3558.74 with 20 work stations.